2021
DOI: 10.3389/fmats.2021.638909
|View full text |Cite
|
Sign up to set email alerts
|

Phytic Acid: Properties and Potential Applications in Dentistry

Abstract: Inositol hexaphosphate (IP6) is the most abundant inositol phosphate in nature and an essential molecule for different biological functions. IP6 has a unique structure granting it distinctive properties; a high negative charge density provides IP6 with an immense chelating ability and valuable antioxidant properties. IP6 is also simple and cost-effective to produce. These features have attracted researchers and entrepreneurs to further study IP6 for a wide variety of applications in areas such as pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 231 publications
(286 reference statements)
0
36
0
Order By: Relevance
“…Despite use of IP6 in several medical, dental, nutritional, and industrial applications, there is limited knowledge concerning its antimicrobial effectiveness and mode of action. Elucidating such effects might result in the development of novel IP6 products for a range of applications, including in endodontics ( Nassar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite use of IP6 in several medical, dental, nutritional, and industrial applications, there is limited knowledge concerning its antimicrobial effectiveness and mode of action. Elucidating such effects might result in the development of novel IP6 products for a range of applications, including in endodontics ( Nassar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phytic acid (IP6) is the major storage form of phosphorus in plant seeds and grain and is extracted using a simple and cost effective process ( Bloot et al, 2021 ). Due to its unique structure and distinctive properties, IP6 lends itself to several dental applications ( Nassar et al, 2021 ), such as dental adhesives ( Nassar et al, 2013 ; Forgione et al, 2021 ) and an endodontic irrigant ( Nassar et al, 2015 ). The high negative charge density of IP6 facilitates chelating activity with cations, thus IP6 has been proposed as an alternative root canal chelating agent with an ability to remove the smear layer, whilst also being biocompatible with osteoblast-like cells ( Nassar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The peculiar structure and the high-density negative charges of IP6 confer a great chelation and unique antioxidant abilities, making it suitable for several applications in dentistry. Despite the compelling data on the merits of IP6 use in dentistry, only very few studies have tested its effect on the bonding of dental adhesive systems to enamel and dentin [24]. We chose to use IP6 in a concentration of 1% on dentin and not higher, based on our pilot study results, where the higher concentrations resulted in an aggressive etching pattern on dentin which negatively affected adhesion (data are not shown).…”
Section: Discussionmentioning
confidence: 99%
“…One of the authors, Aizawa and his colleagues, have reported the fabrication of a novel CPC cement using inositol phosphate (C 6 H 6 (OPO 3 H 2 ) 6 ; IP6) as a chelating agent [ 16 , 17 , 18 ]. IP6 is abundant in grains such as wheat, rice, and corn, and it is commonly used as a food additive [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the phosphate group in IP6 is known to chelate against Ca 2+ ions in HAp. This chelating ability is as strong as that of ethylenediaminetetraacetic acid (EDTA) [ 18 , 21 ]. The chelate-setting cement is mixed with the HAp particles with IP6 surface modification and pure water, and it sets due to the chelating effect of IP6.…”
Section: Introductionmentioning
confidence: 99%